ISOLASI DNA TUMBUHAN LOKAL MELAYU RIAU SEBAGAI RANCANGAN LKPD BERBASIS PENDEKATAN SAINTIFIK PADA MATERI GENETIK SMA KELAS XII - Sirait, Rapika; Mahadi, Imam; Suryawati, Evi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine the results of DNA isolation from seroja and tenggek burung leaves based on the different buffers used namely CTAB, rinso detergent and sunlight soap and produce the worksheet design based on scientific approach in material genetic subject for high school 12th grade. This research was conducted in two stages, namely the experimental activities of DNA isolation and the design worksheet stage of analysis and design. The type of research is laboratory descriptive research. The parameters measured in the study are the presence of DNA and DNA concentration. The results of the study showed that DNA isolation of seroja and tenggek burung leaves was successfully carried out using CTAB buffer and rinso detergent. The presence of DNA can be seen in the supernatant during administration of isopropanol and in the DNA band during electrophoresis. The highest DNA quantity (DNA concentration) was found in the samples of tenggek burung with Rinso detergent TNC detergent of 50 ng/Î¼l and seroja with rinso detergent NC of 20 ng/Î¼l. The DNA quantity using the highest CTAB buffer was found in the CTAB TNC seroja sample of 5 ng/Î¼l and the dead CTAB TNC was 4 ng/Î¼l. While the isolation of DNA with sunlight soap buffer was not successfully carried out. Therefore, it can be concluded that the rinso detergent buffer is more appropriately used for simple DNA isolation experiments in the worksheet designed.Key words: DNA isolation, local plant (seroja and tenggek burung), worksheet